1986
DOI: 10.1111/j.1600-0714.1986.tb00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Class I and Class II major histocompatibility complex antigens on epithelial cells in recurrent aphthous stomatitis

Abstract: The concept of an immunopathogenesis in the establishment and progression of the recurrent aphthous stomatitis (RAS) lesion is well accepted. In this study the expression of Class I and Class II major histocompatibility complex (MHC) antigens on the epithelial cells in the preulcerative, ulcerative and healing phases of RAS lesions was investigated using monoclonal antibodies in an immunohistological technique. Both Class I and Class II MHC antigens were found on the basal cells in preulcerative lesions. As th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 19 publications
2
36
0
1
Order By: Relevance
“…4 The majority are CD45RO + memory cells. 4 Adjacent keratinocytes become HLA-DR 5 and ICAM-1 positive and local blood vessels express Eselectin and VCAM-1. 6 These changes are consistent with release of pro-inflammatory cytokines such as IL-1, IL-6, TNF and interferon-␥.…”
mentioning
confidence: 99%
“…4 The majority are CD45RO + memory cells. 4 Adjacent keratinocytes become HLA-DR 5 and ICAM-1 positive and local blood vessels express Eselectin and VCAM-1. 6 These changes are consistent with release of pro-inflammatory cytokines such as IL-1, IL-6, TNF and interferon-␥.…”
mentioning
confidence: 99%
“…The finding that target antigens are down-regulated by IFN-is intriguing and significant, as the expression of keratinocyte CD54 (intercellular adhesion molecule-1 (ICAM-1)) [44] and HLA-DR [45,46] in ROU lesions suggests that IFN-is being released at ulcer sites, presumably from infiltrating T cells. Down-regulation of AECA target antigens by IFN-has been previously reported in haemolytic uraemic syndrome [21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in patients with aphthous stomatitis there is a heightened lymphocytotoxic effect directed against oral epithelial cells when compared to unaffected controls. [24][25][26] Evidence for this pathogenetic mechanism is also inferred from observations that tissue biopsies of newly erupted aphthous ulcerations demonstrate agglomeration of activated T lymphocytes at the periphery of the lesions, whereas in well-established aphthae the initially predominant CD4…”
Section: Immunologic Factorsmentioning
confidence: 99%
“…[22][23][24] From the observations of several investigators it has been hypothesized that the entire process of aphthous ulceration, from initiation through progression, is instigated by the expression on oral epithelial cells of not only normally found HLA class I antigens but also HLA class II antigens. 25 Presumably, this renders the cells antigenically 'foreign' and consequently they become the targets of a cell-mediated immune reaction perpetrated by lymphocytes and Langerhans cells. It has been shown that in patients with aphthous stomatitis there is a heightened lymphocytotoxic effect directed against oral epithelial cells when compared to unaffected controls.…”
Section: Immunologic Factorsmentioning
confidence: 99%